A compartment burning rate algorithm for a zone model. (January 2016) - Mizukami, T.; Utiskul, Y.; Quintiere, J.G.
Abstract: A model is presented that dynamically predicts the mass loss rate of fuel in a compartment as a function of ventilation, thermal feedback, fuel type and scale. Without a loss of generality, a floor-based fuel is considered. The effect of ventilation is included in the model through the ambient oxygen concentration in the ambient surrounding the fuel at the floor. A mixing model associated with the inlet airflow at the vent is developed to determine this oxygen concentration. An extinction criterion for the flame is based on a critical flame temperature for a diffusion flame associated with the ambient conditions surrounding the flame at the floor. The model is executed in BRI2002, a zone model, capable of computing species and thermal conditions in the upper and lower compartment gas layers. Computations show good agreement with small-scale compartment data for heptane pool fires. The results can accurately portray many regimes of burning including extinction, combustion oscillations, reduction in the flaming area, and quasi-steady burning. Highlights: A MLR model is proposed as a function of ventilation, thermal feedback and scale. The MLR model and algorithms for vent mixing and extinction are added to zone model. Computations show good agreement with small-scale experiments for heptane pool fires. The results can portray extinction, combustion oscillation, and quasi-steady burning. MLR: mass loss rate of fuel.